Enhancing ESP Learning: Investigating Students' Perspectives on Real-Time Written Corrective Feedback Delivery via Google Docs - Susilawati; Nurhasanah Halim; Retno Dwigustini; Samah Rashad Abdallah Alakhali (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2024)
The present research aims to investigate the practice of real-time or synchronous written corrective feedback (SWCF) delivery via Google Docs as a platform to deliver feedback, known as a linguistic feedback tool (LiFT) in ESP (English for Specific Purposes) classes, students’ preferences and viewpoints of SWCF. The research employed a qualitative case study involving 15 students from an advanced English correspondence course in a non-English department of a private university in Depok, West Java, Indonesia. Open-ended questionnaires, document analysis, and semi-structured interviews were used to gather the data. The findings revealed that auto-generated and human feedback are used to deliver SWCF via Google Docs, inferring that those features can build students' awareness of language aspects, content, and context in composing professional documents. Direct feedback was delivered more frequently, regarding the learning time efficiency and the students’ ability to identify errors. Further, the students preferred frequent SWCF, direct and indirect feedback, and correcting delivery methods. Finally, they considered that SWCF delivered via Google Docs assists them in improving letter accuracy. Their preferences and viewpoints might allow the lecturer to choose appropriate feedback delivery strategies and material reinforcement. The present research implies a balanced use of auto-generated and human feedback from LiFT in SWCF delivery. Evaluating the effectiveness of SWCF delivery via Google Docs for different levels of achievers in ESP classes might be a potential area of future research. Other LiFTs’ infusion into ESP classes is also worth researching to provide language instructors with alternative applications for SWCF delivery.